Flunixin meglumine tissue residues after intravenous administration in goats - Giles, Claire B.; Ferdous, Farha; Halleran, Jennifer L.; Yeatts, Jim L.; Baynes, Ronald E.; Mzyk, Danielle A. (Frontiers in Veterinary Science, 2024)
Background Flunixin is commonly used in goats in an extra-label manner, indicating a significant need to determine withdrawal intervals for edible tissues. Objective The objectives of the present study were to investigate the depletion of flunixin meglumine in various goat tissues, including the liver, kidney, fat, and muscle. Methods Twenty Boer goats were enrolled and administered an intravenous dose (2.2 mg/kg) of flunixin meglumine. Five animals were randomly euthanized at 24, 48, 72, or 96 h following dosing. All samples were analyzed via ultra-performance liquid chromatography coupled with mass spectrometry. Results The concentration of flunixin in all tissues declined rapidly, with the highest mean concentrations quantified in the kidney (0.137 ± 0.062 μg/g) and liver (0.077 ± 0.029 μg/g) tissues at 24 h. Conclusion Since any detection of flunixin residues at slaughter found in goat tissues is considered a violative residue, a conservative withdrawal interval of 17 days was calculated to ensure levels of flunixin fell below the regulatory limits of detection in liver, kidney, and muscle tissues.